Variations of southeast Vatnajökull ice cap (Iceland) 1650–1900 and reconstruction of the glacier surface geometry at the Little Ice Age maximum. Issue 2 (8th October 2014) - Hannesdóttir, Hrafnhildur; Björnsson, Helgi; Pálsson, Finnur; Aðalgeirsdóttir, Guðfinna; Guðmundsson, Snævarr
Abstract We present an overview of glacier variations of the outlet glaciers of southeast Vatnajökull ice cap, Iceland, during the time period ∼1650–1900 as represented in historical archives, by geomorphological field evidence and assess the timing of the Little Ice Age (LIA) maximum. According to written documents, all glaciers advanced in the latter half of the seventeenth century and extended far out on the lowlands in the mid‐eighteenth century. Contemporary documents describe how all the studied glaciers were at their LIA terminal moraines around ∼1880–1890 (no descriptions found for Morsárjökull) and soon after started receding, marking the end of the LIA in Iceland. Reconstruction of the LIA maximum glacier surface geometry was based on glacial geomorphological features (including lateral and terminal moraines, trimlines and erratics), historical photographs, maps from 1904, and a 2010 LiDAR digital elevation model. The glaciers were at their LIA maximum around 150–270 m thicker near the terminus than in 2010, whereas negligible differences were observed in the upper reaches of the accumulation area. By combining the historical, glacial geomorphological and high‐resolution LiDAR data, we provide quantitative estimates of the glacial extent and volume at the LIA maximum. The highest up‐valley lateral moraines provided estimates of the equilibrium line altitude (ELA) during the LIA, which was on average 340 m lower than the present day ELA. Consistency was found in the spatial variability of the ELA during both time periods, with higher values on the westfacing outlets of Öræfajökull ice cap (at the southern end of Vatnajökull ice cap), than on the east flowing glaciers, and a rise in the ELA from west to east on the outlets east of Breiðamerkurjökull.